THE EFFECT OF FINANCIAL PERFORMANCE ON THE VALUE OF COAL MINING COMPANIES IN INDONESIA WITH MODERATION OF COAL PRICE - Edison Hasibuan, Pangeran
Company value is very important because it will affect investors' decisions to invest in the company. One of the factors that can affect the value of the company is the company's financial performance. In this study, the effect of financial performance on the value of coal mining companies in Indonesia will be analyzed. The variables used in measuring financial performance are profitability ratios, activity, liquidity, and solvency. Coal price is used as a moderating variable that will affect the relationship between financial performance on company value. The method used in analyzing and processing the data is moderated regression analysis with a structural equation modeling (SEM) model using the SmartPLS software. The samples observed were coal mining companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The results showed that financial performance proxied by profitability had a positive and significant effect, activity had a positive and insignificant effect, liquidity had a negative and insignificant effect, solvency had a negative and insignificant effect on firm value. Meanwhile, the moderating impact of coal prices only strengthens the effect of financial performance proxied by profitability on company value.